2019
DOI: 10.3892/etm.2019.7694
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin D plus calcium with/without alendronate on bone metabolism in immunologic thrombocytopenic purpura patients with steroid treatment: Nine‑month results of a randomized, double‑blinded, controlled trial

Abstract: Bone loss is a prominent complication in immunologic thrombocytopenic purpura (ITP) patients with steroid treatment. Anti-osteoporotic medications are applied as a therapeutic strategy to prevent bone deterioration in ITP patients. However, the skeletal protective effect of alendronate (ALN) in ITP patients has been rarely reported. The present study was performed to determine whether ALN reduces bone loss in ITP patients. A total of 40 ITP patients with steroid treatment were randomized into a placebo group [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has been reported that the incidence of respiratory tract infection during treatment in ITP patients is as high as 5 times that of healthy people, and the mortality rate within 1 year of treatment is as high as 0.9%. The majority of deaths were from upper respiratory tract infection (URI) [ 6 ]. Therefore, while paying close attention to complications such as severe bleeding in ITP, we must also pay attention to the prevention and treatment of respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the incidence of respiratory tract infection during treatment in ITP patients is as high as 5 times that of healthy people, and the mortality rate within 1 year of treatment is as high as 0.9%. The majority of deaths were from upper respiratory tract infection (URI) [ 6 ]. Therefore, while paying close attention to complications such as severe bleeding in ITP, we must also pay attention to the prevention and treatment of respiratory tract infections.…”
Section: Introductionmentioning
confidence: 99%